2001
DOI: 10.1161/hc3701.096064
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Coronary Stent Implantation Under Ultrasound or Angiographic Guidance to Reduce Stent Restenosis (OPTICUS Study)

Abstract: for the OPTICUS (OPTimization with ICUS to reduce stent restenosis) Study InvestigatorsBackground-Observational studies in selected patients have shown remarkably low restenosis rates after ultrasoundguided stent implantation. However, it is unknown whether this implantation strategy improves long-term angiographic and clinical outcome in routine clinical practice. Methods and Results-A total of 550 patients with a symptomatic coronary lesion or silent ischemia were randomly assigned to either ultrasound-guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
126
3
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(137 citation statements)
references
References 33 publications
3
126
3
5
Order By: Relevance
“…Generally, greater acute gain produces more injury and more late loss. However, similar to other reports, 14 it did not result in increased late loss in the IVUS-guided group in the present study. Analogous to our findings regarding stent length and restenosis, we tend to ascribe this effect to optimization of the luminal geometry.…”
Section: Oemrawsingh Et Al Ivus Improves Outcome Of Long Stent Implansupporting
confidence: 92%
See 1 more Smart Citation
“…Generally, greater acute gain produces more injury and more late loss. However, similar to other reports, 14 it did not result in increased late loss in the IVUS-guided group in the present study. Analogous to our findings regarding stent length and restenosis, we tend to ascribe this effect to optimization of the luminal geometry.…”
Section: Oemrawsingh Et Al Ivus Improves Outcome Of Long Stent Implansupporting
confidence: 92%
“…11 However, randomized studies investigating this strategy have yielded inconsistent results. [12][13][14][15][16][17] We hypothesized that the potential advantages of IVUS guidance would be most apparent in complex lesions, such as long stenoses. In this report, we compared the clinical and angiographic outcome after stenting of long coronary artery stenoses with randomization to angiographic or IVUS guidance of the intervention.…”
mentioning
confidence: 99%
“…8,9 However, the impact of IVUS on clinical outcomes has been controversial according to different lesion subsets. [10][11][12] Long-term clinical benefits of IVUS guidance during PCI at bifurcation lesions are especially uncertain and need further investigation. Therefore, we evaluated the long-term clinical usefulness of IVUS during PCI with DES for coronary bifurcation lesions using data from a dedicated multicenter registry.…”
mentioning
confidence: 99%
“…The DIPO study 11) and the TULIP study 12) also suggested that IVUS-guided PCI could reduce restenosis and MACE. However, the OPTICUS study 13) did not show an effect of IVUS guidance on restenosis. The OPTICUS study investigators explained that the unexpectedly good acute results in the angiographic-guided group were due to the extensive experience with IVUS among the OPTICUS investigators, which might have affected the method used to implant the stents under angiographic guidance.…”
Section: Discussionmentioning
confidence: 88%